A Model of the Development Public Mind Empowerment of Early Childhood according to the King’s Philosophy - Thongpun, Maneerat; Thaothumma, Seksun (Journal of Humanities and Social Sciences Nakhon Pathom Rajabhat University, 2024)
A Model of the Development Public Mind Empowerment of Early Childhood according to the King’s Philosophy is an activity to increase willpower and public child. It is an activity that uses the royal science to develop the public mind of early childhood children in terms of public mind in society It is an activity that encourages early childhood children to express the behavior of public mind in society in their daily lives through the learning process in organizing experiences in daily life. Teachers designed age-appropriate activities to integrate knowledge of the king’s science in morality and ethics which is the basic behavior that manifests itself in social activities together. There are 5 activities for the public child that make early childhood children have a public mind according to the king’s science are to join and cooperate in making benefits for society and the public, kindness, helping, sharing, taking responsibility for oneself and society.